Identification of duplicates in the germplasm of sweet potato (Ipomoea batatas (L.) Lam.) using morphological and molecular markers - Anil, Shirly; Babu, Babitha; Radhika, Krishna; Devi, Asha; Krishnan, Prakash; J, Sreekumar (JOURNAL OF ROOT CROPS, 2022)
Fifty accessions of sweet potato from National Active germplasm site of ICAR-CTCRI were selected for morphological and molecular analysis and to identify duplicates. Morphological analysis was performed by using twenty IPGRI descriptors. The data analysed using R package separated the accessions into five principal clusters at a Euclidean distance of 15 and resulted in the identification of three pairs of morphological duplicates (S-236 and S-256, S-203 and S-295, S-772 and S-747). The PCA analysis revealed predominant vine colour and secondary vine colour, abaxial vein pigmentation and petiole pigmentation as the major factors that contributed to the clustering of the sweet potato accessions. Molecular characterization using 11 ISSR primers resulted in 162 polymorphic bands with a mean value of 14.7 bands per primer. The dendrogram based on ISSR markers dendrogram grouped the accessions into six clusters at a Jaccard distance of 0.9. The third principal cluster comprised of 20 accessions which were assembled in 5 sub-groups which indicates high intraclusteral variability. The fourth principal cluster comprised of 15 accessions in 4 groups. In this principal cluster S-236 and S-256 grouped together with 100% similarity. This pair can be considered as true duplicates which were also found similar in morphological characterization. The similarity between the different accessions ranged between 52-100%. The least similar accessions were SD-39 and S-298 (52%). Thus it can be inferred that maximum of 48% variability existed within the selected accessions which can be considered as a low to moderate diversity. Based on morphological and molecular analysis three pairs of duplicates were identified and may be culled out from the germplasm.